SIFAT KIMIA DAN SENSORI SELAI KULIT KOPI PADA BERBAGAI KONSENTRASI ASAM SITRAT DAN GULA KRISTAL PUTIH - Randi Aziz Al-farisi; Sussi Astuti; Sri Hidayati; Tanto Pratondo Utomo (Jurusan Teknologi Hasil Pertanian, 2026)
Coffee skin is an agricultural byproduct that has the potential to be processed into value-added food products such as jam. Coffee skin can be made into jam because it has a pectin content of 27.20-57.24%. The study aims to determine the effect of the addition of citric acid and white crystal sugar, as well as their interaction on the chemical and sensory properties of coffee skin jam. The study was arranged in a Completely Randomized Block Design (CRBD) with two factors and three replications. The first factor was the addition of citric acid with 2 concentration levels of 0.5% (A1) and 0.9% (A2) and the second factor was the addition of white crystal sugar with 4 concentration levels of 40% (G1), 50% (G2), 60% (G3), and 70% (G4). Data homogeneity was tested using the Bartlett test, data addition using the Tuckey test, then the data were analyzed for variance to determine the effect between treatments and further analysis using Honestly Significant Difference (HSD) at the 5% level. The results showed that the interaction of citric acid and white crystal sugar had a very significant effect on water content, color (L*, a*, b*), color score, taste, texture and overall acceptance. The concentration of white crystal sugar had a very significant effect on the total soluble solids and spreadability of coffee skin jam. Treatment A2G3 (AS 0.9% and GK 60%) was the most preferred combination of citric acid and white crystal sugar coffee skin jam.